A new species of Raspy cricket genus Gryllacris (Orthoptera: Gryllacrididae) from Central India - Gupta, Sunil Kumar; Chandra, Kailash (Zootaxa, 2017)
Gryllacris durgensis sp. nov. is described from the Durg district, Chhattisgarh, India. The detailed morphological characters of adult male, female and nymph are provided.